2020
DOI: 10.14814/phy2.14571
|View full text |Cite
|
Sign up to set email alerts
|

Doxycycline preserves chondrocyte viability and function in human and calf articular cartilage ex vivo

Abstract: Prolonging chondrocyte survival is essential to ensure fresh osteochondral (OC) grafts for treatment of articular cartilage lesions. Doxycycline has been shown to enhance cartilage growth, disrupt terminal differentiation of chondrocytes, and inhibit cartilage matrix degradation. It is unknown whether doxycycline prolongs chondrocyte survival in OC grafts. We hypothesized that doxycycline protects against chondrocyte death and maintains function of articular cartilage. To test this hypothesis, we employed huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Other studies did not demonstrate this same chondrotoxicity. 18,19 For instance, Yue et al 23 found that doxycycline decreased chondrocyte apoptosis, increased type II collagen synthesis, and increased mechanical integrity. Doxycycline has also been shown to protect the articular environment through decreased expression of catabolic cytokines.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies did not demonstrate this same chondrotoxicity. 18,19 For instance, Yue et al 23 found that doxycycline decreased chondrocyte apoptosis, increased type II collagen synthesis, and increased mechanical integrity. Doxycycline has also been shown to protect the articular environment through decreased expression of catabolic cytokines.…”
Section: Resultsmentioning
confidence: 99%
“…Chondrocyte viability plays a critical role in maintaining the biochemical and biomechanical properties necessary to prevent stenosis or collapse in tracheal replacement, however the preservation of chondrocyte viability remains a challenge in tracheal tissue engineering. 19,41,42 Modulation of decellularization protocol, such as optimization of decellularization time, can preserve viability of chondrocytes in DTS. 19 We also observed a higher mortality rate of hosts receiving DTS than that of STG control (p = 0.0490).…”
Section: Discussionmentioning
confidence: 99%
“…Chondrocytes are responsible for the maintenance of the graft matrisome; the viability of these cells could prove to play a critical role in graft performance. [28][29][30] Beyond decellularization, graft viability is related to ischemia time and storage conditions; these factors can limit the creation of a donor tissue bank. Wellestablished approaches of cryopreservation methods to biobank organs have been developed to enhance viability.…”
Section: Discussionmentioning
confidence: 99%
“…Graft chondrocyte viability is now a new and important consideration. Chondrocytes are responsible for the maintenance of the graft matrisome; the viability of these cells could prove to play a critical role in graft performance 28–30 . Beyond decellularization, graft viability is related to ischemia time and storage conditions; these factors can limit the creation of a donor tissue bank.…”
Section: Discussionmentioning
confidence: 99%